CULTURAL ARTIFACTS IN STUDENTS’ LITERACY NARRATIVE - R. R Setyaningrum (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2019)
Literacy narrative is students’ writing. The students write their experiences in pass about how they learn reading, writing, speaking or listening in English. Students’ literacy narrative tells their effort to change identity from positional identity to figurative identity by using cultural artifacts. This study presents to identify the cultural artifacts to improve the students’ figurative identity through students’ literacy narrative. The objectives of study are to identify the cultural artifacts that use to change their identity by using literacy narrative. Qualitative research used to identify the cultural artifacts through students’ literacy narratives assignment and interview. The samples of the study are 20 students of senior high school. The finding result showed cultural artifacts are as tools to change their identity as a poor writer to be a good identity. Based on the students’ literacy narrative almost all of the students change their identity by cultural artifacts as books and English program (extracurricular). But some others, they joined English course beyond the school’s program. Considering the findings, this research highlights the need several times to identify the kinds of students’ identity by using ethnography.